"Análisis de costos y rentabilidad en proyectos de producción porcina de la finca la María de la Universidad Técnica Estatal de Quevedo del período". 2012-2014 - Tuárez Rodríguez, Lilia Juliana (2016)
This research project entitled " ANALYSIS OF PROJECT COSTS AND PERFORMANCE OF PIG FARM PRODUCTION THE MARY State Technical University Quevedo PERIOD 2012 - 2014.fue held in the city of Quevedo what is sought with this study is know the exact cost and profitability obtained from pig farm program that is located within the premises of the state technical University of Quevedo on the farm the boiler. To perform this research was sampled population, employees and workers are part of this program getting information through interviews, direct observation and knowledge acquired during visits to the "La Maria” State Technical University of Quevedo. The current study contains the objectives Program Unit study, the current situation in terms of the number of copies are there at this time related to players , : Besides sales of pigs detailed in the years 2012, 2013 and 2014 , pointing out that types of costs are affected the program, the income generated in the years of production . KEYWORDS: Analysis, Costs and profitability